2010
DOI: 10.1007/s12348-010-0007-5
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative photoreceptor cell damage in autoimmune uveitis

Abstract: Uveitis comprises an extensive array of intraocular inflammatory diseases and often results in irreversible visual loss. Experimental autoimmune uveitis (EAU) is an animal model used to study human uveitis. Both innate and adaptive immune responses are known to mediate retinal damage in EAU. The innate immune response occurs first with activation of toll-like receptors which upregulate inflammatory cytokines, leading to oxidative stress; subsequently, the adaptive immune response results in inflammatory cytoki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 33 publications
(70 reference statements)
0
17
0
1
Order By: Relevance
“…We observed that TCDD treatment suppressed the levels of pro-inflammatory cytokines TNF-α, IL-6, and IL-1β. This anti-inflammatory effect of TCDD may be due to its modulation of macrophages/microglia, as the activated M1 subset accelerates inflammation and causes tissue damage by increasing the secretion of multiple pro-inflammatory cytokines such as TNF-α, IL-6, and the release of reactive oxygen species, resulting in the nitration of cytochrome c which is known to cause apoptosis ( 7 , 17 , 18 ). These findings indicate that the anti-inflammatory effect of AhR may contribute to its protection on BRB as well as the control of apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…We observed that TCDD treatment suppressed the levels of pro-inflammatory cytokines TNF-α, IL-6, and IL-1β. This anti-inflammatory effect of TCDD may be due to its modulation of macrophages/microglia, as the activated M1 subset accelerates inflammation and causes tissue damage by increasing the secretion of multiple pro-inflammatory cytokines such as TNF-α, IL-6, and the release of reactive oxygen species, resulting in the nitration of cytochrome c which is known to cause apoptosis ( 7 , 17 , 18 ). These findings indicate that the anti-inflammatory effect of AhR may contribute to its protection on BRB as well as the control of apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Although safer, this strategy would not completely eliminate the risk. Sympathetic ophthalmia is a rare disease in which surgery or injury to one eye incites an immune reaction that causes an inflammatory injury to the patient’s contralateral or sympathetic eye 69 70 . Despite aggressive immune suppression, some cases of sympathetic ophthalmia can result in irreversible blindness 71 .…”
Section: Discussionmentioning
confidence: 99%
“…From multiple studies conducted in rodent EAU, backed by research using diseased human eyes, an important role for oxidative stress in posterior uveitis has been recognized (Nguyen and Rao, 2011; Rao, 1990). A key player is nitric oxide, which is produced from arginine and oxygen through the action of inducible nitric oxide synthase (NOS2) or constitutively expressed neuronal (NOS1) and endothelial (NOS3) forms (Lowenstein et al, 1994).…”
Section: Autoimmune Posterior Uveitismentioning
confidence: 99%